Trail guide to the body - Andrew Biel (Andrew Biel, 1997)
This acclaimed book teaches readers to palpate the body's structures with ease and precision. The beautifully illustrated, user-friendly guide to the muscular and skeletal systems makes learning the necessary bodywork skills interesting, memorable and easyThis acclaimed book teaches readers to palpate the body's structures with ease and precision. The beautifully illustrated, user-friendly guide to the muscular and skeletal systems makes learning the necessary bodywork skills interesting, memorable and easy